Personality of the Main Character in Eat,Pray,Love Novel by Elizabeth Gilbert - Ramadani, Dian; Valientien, Nita Maya; Max, Jonathan Irene Sartika Dewi (Fakultas Ilmu Budaya Universitas Mulawarman, 2023)
Psychoanalysis is a theory that is used to analyze the human psyche where the behavior that occurs is due to the mindset that is controlled under the human consciousness. One that can be influenced is the human personality which is described through literary works such as a novel. The purpose of this study is to identify how the personality of the main character depicted in Eat, Pray, Love novel. The researcher uses qualitative methods. The data used in this study are utterances and dialogues. The results of this study indicate that there are three aspects of personality structure found in Eat, Pray, Love novel. The aspects are id (biological aspect) has a role to fulfill the inner satisfaction to get pleasure, ego (rational aspect) plays a role in controlling the inner satisfaction by the id and prioritizes reality, and superego (moral aspect) focuses on morality where it comes from parental teachings and norms that exist in society. These three aspects bridge other to regulate the steps taken by Elizabeth as the main character in the novel.